Functional imaging of human retina using integrated multispectral and laser speckle contrast imaging. Issue 2 (21st November 2021) - Feng, Ximeng; Yu, Yue; Zou, Da; Jin, Zi; Zhou, Chuanqing; Liu, Gangjun; Fujimoto, James G.; Li, Changhui; Lu, Yanye; Ren, Qiushi
Abstract: A novel integration of retinal multispectral imaging (MSI), retinal oximetry and laser speckle contrast imaging (LSCI) is presented for functional imaging of retinal blood vessels that could potentially allow early detection or monitoring of functional changes. We designed and built a cost‐effective, scalable, retinal imaging instrument that integrates structural and functional retinal imaging techniques, including MSI, retinal oximetry and LSCI. Color fundus imaging was performed with 470 nm, 550 nm and 600 nm wavelength light emitting diode (LED) illumination. Retinal oximetry was performed using 550 nm and 600 nm LED illumination. LSCI of blood flow was performed using 850 nm laser diode illumination at 82 frames per second. LSCI can visualize retinal and choroidal vasculature without requiring exogenous contrast agents and can provide time‐resolved information on blood flow, generating a cardiac pulse waveform from retinal vasculature. The technology can rapidly acquire structural MSI images, retinal oximetry and LSCI blood flow information in a simplified clinical workflow without requiring patients to move between instruments. Results from multiple modalities can be combined and registered to provide structural as well as functional information on the retina. These advances can reduce barriers for clinical adoption, accelerating research using MSI, retinal oximetry and LSCI of blood flow for diagnosis, monitoring and elucidating disease pathogenesis. Abstract : An integrated, scalable retinal‐imaging instrument provides multiple dimensions of retinal structural and functional information in a simplified clinical workflow, reducing barriers for clinical adoption and accelerating research using these imaging tools for diagnosis, monitoring and elucidating disease pathogenesis.